1989
DOI: 10.1017/s0950268800029678
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuniisolations from Mexican and Swedish patients, with repeated symptomatic and/or asymptomatic diarrhoea episodes

Abstract: The presence of different Campylobacter jejuni serotypes in Swedish patients with diarrhoea and in Mexican patients with or without diarrhoea was investigated with special reference to repeated isolations during the course of infection and to symptomatic and asymptomatic episodes. The study included 136 C. jejuni isolates from 62 Mexican children and 173 isolates from 68 Swedish patients. The bacteria were serotyped for heat-stable (HS) and heat-labile (HL) antigen. Swedish patients, all with symptoms, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…These serogroups have commonly been associated with handling and\or consumption of chicken and cattle [14,19,27]. From this study, as in a former one [13], we also found that children in developing countries frequently carry more than one campylobacter strain at one occasion. From approximately 20 % of the cases more than one strain could be identified, both in regard to the species identification as well as to the serotyping [25].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…These serogroups have commonly been associated with handling and\or consumption of chicken and cattle [14,19,27]. From this study, as in a former one [13], we also found that children in developing countries frequently carry more than one campylobacter strain at one occasion. From approximately 20 % of the cases more than one strain could be identified, both in regard to the species identification as well as to the serotyping [25].…”
Section: Discussionsupporting
confidence: 72%
“…Major questions in investigations of campylobacter hitherto have been directed towards understanding the sources of campylobacter infection as well as the mode of transmission of the bacteria. Poultry appears to be a significant source of campylobacter [13,18,19]. Different serotyping systems have been developed to provide additional markers in the study of the epidemiological features of these organisms [4][5][6][7][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In another study, there was no difference in serotypes isolated from symptomatic and asymptomatic children. 15 The main explanation for the different disease expression in developing versus developed countries has been the early acquisition of immunity by children exposed to hyperendemic and/or polymicrobial infection. 16−18 There is documentation of concurrent infections precipitating C. jejuni enteritis.…”
Section: Introductionmentioning
confidence: 99%